Aplicação da espectroscopia de lente térmica para a avaliação da fotoestabilidade de óleos vegetais - Savi, Elton de Lima (2013)
Vegetable oils are known to be unstable when exposed to light and, consequently, undergo photochemical reaction. For the determination of photostability of these oils it is then of outmost importance the proper identification of the photo-induced degradation processes. In this work, the photostability of vegetable oils is investigated by Thermal Lens Spectroscopy (TLS). The results obtained using TLS are compared to optical spectroscopy measurements. Vegetable oils are prepared with different natural and synthetic antioxidants, and the measurements at room temperature. The TLS experiments are performed at different excitation wavelength, and the results show both the presence of photochemical reaction and mass diffusion processes during laser excitation. The contributions to the thermal lens signal are modeled numerically, and the physical and chemical properties of the samples are quantitatively determined. With the determination of the photochemical reaction cross-section of the sample, we were able to quantify the photostability of the samples for the different antioxydants. The results presented here demonstrate that time-resolved thermal lens spectroscopy can be used as a very sensitive analytical tool for quantitative measurement of photo-induced chemical reaction processes in solutions.